NF-κB pathways in hematological malignancies. - Gasparini, Chiara; Celeghini, Claudio; Monasta, Lorenzo; Zauli, Giorgio (Cell Mol Life Sci, 2014)
The nuclear factor κB or NF-κB transcription factor family plays a key role in several cellular functions, i.e. inflammation, apoptosis, cell survival, proliferation, angiogenesis, and innate and acquired immunity. The constitutive activation of NF-κB is typical of most malignancies and plays a major role in tumorigenesis. In this review, we describe NF-κB and its two pathways: the canonical pathway (RelA/p50) and the non-canonical pathway (RelB/p50 or RelB/p52). We then consider the role of the NF-κB subunits in the development and functional activity of B cells, T cells, macrophages and dendritic cells, which are the targets of hematological malignancies. The relevance of the two pathways is described in normal B and T cells and in hematological malignancies, acute and chronic leukemias (ALL, AML, CLL, CML), B lymphomas (DLBCLs, Hodgkin's lymphoma), T lymphomas (ATLL, ALCL) and multiple myeloma. We describe the interaction of NF-κB with the apoptotic pathways induced by TRAIL and the transcription factor p53. Finally, we discuss therapeutic anti-tumoral approaches as mono-therapies or combination therapies aimed to block NF-κB activity and to induce apoptosis (PARAs and Nutlin-3).
Keywords: Antineoplastic Agents; B-Lymphocytes; Carcinogenesis; Dendritic Cells; Gene Expression Regulation, Neoplastic; Hematologic Neoplasms; Humans; Imidazoles; Macrophages; NF-kappa B; Piperazines; Signal Transduction; T-Lymphocytes; TNF-Related Apoptosis-Inducing Ligand; Transcription Factor RelA; Transcription Factor RelB; Tumor Suppressor Protein p53